EFFECT OF SEASON ON REPRODUCTIVE PERFORMANCE OF BUFFALOES AT AN ORGANIZED FARM
· Calving records of 773 Murrah buffaloes for the period from 2000 to 2007 at an organised farm of National Dairy Research Institute, Kamal, Haryana, India was analyzed to study the effect of season on reproductive performance traits of the herd. The overall Days open, Days to first service (DFS), Services per conception (SC), Breeding interval (Bl), Breeding interval between first and second service (Bl1 ), Breeding interval between second and third service (Bl2), Breeding interval between third·and fourth. service (Bl3), Breeding interval between fourth and fifth service (Bl4) and Breeding interval between fifth and sixth service (Bl5) of Murrah buffalo in the herd were found to be 170.32 ± 4.67, 91.89 ± 1.99, 2.05 ± 0.05, 74.70 ± 0.08, 73.57 ± 2.98, 82.96 ± 4.00, 67.68 ± 4.40, 72.63 ± 8.31 and 66.73 ± 13.69, respectively. Days open (183.13 ± 8.12